Macroinsurance for Microenterprises : A Randomized Experiment in Post-Revolution Egypt - Groh, Matthew; McKenzie, David (World Bank Group, Washington, DC, 2014)
Firms in many developing countries cite macroeconomic instability and political uncertainty as major constraints to their growth. Economic theory suggests uncertainty can cause firms to delay investments until uncertainty is resolved. A randomized experiment was conducted in post-revolution Egypt to measure the impact of insuring microenterprises against macroeconomic and political uncertainty. Demand for macroeconomic shock insurance was high; 36.7 percent of microentrepreneurs in the treatment group purchased insurance. However, purchasing insurance does not change the likelihood that a business takes a new loan, the size of the loan, or how the loan is invested. This lack of effect is attributed to microenterprises largely investing in inventories and raw materials rather than irreversible investments like equipment. These results suggest that, contrary to what some firms profess, macroeconomic and political risk is not inhibiting the investment behavior of microenterprises. However, insurance may still be of value to help firms cope with shocks when they do occur, but the paper is unable to examine this dimension, because the insurance product did not pay out over the course of the pilot.